Nursing Leadership in a Post-Pandemic Elective Orthopaedic Theatre Department: A Detailed Thematic Analysis of an Open-Ended Qualitative Survey - Carlo Biz; Lisa Buffon; Davide Scapinello; Sean Semple; Elisa Belluzzi; Ron Batash; Pietro Ruggieri (Nursing Reports)
Background: The COVID-19 pandemic has impacted nursing theatre staff, departmental activity, and delivery of services to patients. This work-based project aimed to investigate the challenges of nursing leadership in an elective orthopaedic department at current times. Methods: The study collected qualitative data exploring theatre staff’s expectations from leadership, offering insight on how the pandemic has influenced the way of working and exploring how the future in this unit may look. The answers from 20 practitioners to an anonymised open-ended survey were examined using thematic analysis. Results: The participants described a leader as a good communicator who focuses on empowering others and supporting the team, identified by the majority as a senior team member. From the findings, three topics were identified: immediate changes, delayed changes, and pre-existing conditions. The answers painted a reality that is complex and multifaceted, where numerous variables play a part in the physical and mental health of each candidate, impacting their performance as well as their work/life balance. Overall, the strongest subjects recurring in the findings were the need for nursing leadership to focus on supporting staff with training opportunities, to actively plan for a reduction in staffing shortages, and to be constantly mindful of staff well-being. Conclusions: This study pointed out that the need for constant communication with their staff, building honest relationships, and being a reliable leader, focused on empowering others and supporting the team were important factors for the nursing management during the COVID-19 pandemic and post-COVID-19 era.